ORIF Patella Fracture With a Tension Band Construct. (August 2017) - Blum, Laura; Hake, Mark
Abstract : Summary: Patellar fractures can occur as a result of direct or indirect injuries. Indirect injury is more common and occurs when the patella fails in tension when the force exerted by the extensor mechanism exceeds that of the bone. Common mechanism of indirect injury is rapid knee flexion with fully contracted quadriceps muscle. Treatment with a tension band construct is indicated for transverse patella fractures without significant comminution. This can be performed with 18-gauge wire and either 2 parallel, longitudinally oriented cannulated screws or 2 Kirschner wires. Biomechanical studies have shown higher load to failure when performed with cannulated screws. We presented our technique for management of a transverse patella fracture with disrupted extensor mechanism using tension banding technique with cannulated screws.